Eficácia de diferentes combinações de antígenos e adjuvantes na indução da resposta imune humoral em jundiás (Rhamdia quelen) - Pavan, Tatiana Rohde (2015)
In this work we evaluated the immune response of silver catfish (Rhamdia quelen) following the inoculation of different combinations of antigens and adjuvants. In chapter 1 we investigated the potential of inactivated Parapoxvirus ovis (iPPVO) as immunomodulator of the innate immune response and production of antibodies to bovine serum albumin (BSA). The respiratory burst of silver catfish juvenile (60 80 g) inoculated with iPPVO (1 x 106 plaque forming units PFU) was similar, at 24 h post-inoculation (p.i.), to the control fish inoculated with sterile phosphate buffered saline (PBS) solution. However, significant differences (p < 0.05) were observed on circulating monocytes, heterophils and thrombocytes at 3, 5 and 7 days p.i., respectively in iPPVO inoculated silver catfish. Furthermore, silver catfish inoculated with iPPVO+BSA (200 μg/fish) had significantly (p < 0.05) higher antibody titers to BSA compared to fish inoculated with BSA+PBS, indicating its adjuvanticity effect on antibody production. In chapter 2 we report the use of different combinations of traditional adjuvants (aluminum hydroxide, Freund complete adjuvant, Freund incomplete adjuvant, and montanide), and new generation adjuvants, composed of olygodeoxynucleotides CpG (ODN CpGs) associated with Aeromonas hydrophila bacterin, or BSA, on the production of specific antibodies. In these experiments, juvenile catfish (60 80 g) were inoculated once with 0,2 ml of each antigen (A. hydrophila, 1 x 108 colony forming unit CFU, or BSA 200 μg) and the production of antibodies was determined at 42 days p.i. in the groups inoculated with A. hydrophila, and at 14, 28 and 42 days p.i. for the groups inoculated with BSA. Control groups consisted of fish inoculated with the antigens and sterile PBS. All immunized fish seroconverted to A. hydrophila; however, there was a significant difference (p <0.05) between the control group and the remaining inoculated groups. And, amongst the A. hydrophila inoculated groups there was a significantly lower (p < 0.05) antibody titer in the group of fish inoculated with A. hydrophila + ODN CpG 1668 compared to the groups inoculated with A. hydrophila + CpG 2133, CpG 2102 and CpG 2143. Fish inoculated with BSA combined with different adjuvants, all fish seroconverted and there were significant differences (p < 0.05) in the antibody titers at 14, 28 and 42 days p.i. The difference in antibody titers were observed either in fish within the same group at different days p.i., or when compared within different groups in the same day p.i. In general, higher antibody titers to BSA were observed at 28 days p.i. Within the classical adjuvants, the higher anti-BSA antibody titers were observed in fish inoculated with a combination of BSA+Freund complete adjuvant. And, within the ODN CpGs adjuvants, higher anti-BSA antibody titers were observed in fish inoculated with BSA+CpG 1668. The studies reported herein indicate that iPPVO might be exploited as immunomodulator in fish and that ODN CpGs adjuvants stimulated the production of specific antibodies in silver catfish at titers similar or even higher than those stimulated by classical adjuvants